Frontiers of the Roman Empire : = Grenzen des Römischen Reiches = Frontières de l'Empire Romain - Breeze, David J; Thiel, Andrea; Roth, Sarah; Becker, Thomas (2022)
This text illustrates the historical and archaeological significance of the Upper Germanic Limes and provides an up-to-date overview of its manifold features in the field.